2005
DOI: 10.1016/s0148-2963(03)00122-x
|View full text |Cite
|
Sign up to set email alerts
|

Trust and commitment influences on customer retention: insights from business-to-business services

Abstract: Despite the importance of trust and commitment in relationship marketing, the scholarly inquiry on the issue is rather impeded in several ways. Furthermore, when it comes to the marketing of services, and specifically for business-to-business markets, the empirical documentation is even slimmer despite the fact that services are increasingly becoming a vital component of the product that the customers buy even when it comes to tangible goods such as computers or cars. In view of this gap, the present empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
380
2
38

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(433 citation statements)
references
References 65 publications
13
380
2
38
Order By: Relevance
“…There are also some evidences supporting a positive relationship between e-tailer trust and e-loyalty, in term of increased spending [44], and intentions to purchase [45] or repurchase. E-trust also have positive and significant influence on e-commitment [46].…”
Section: Trustmentioning
confidence: 90%
“…There are also some evidences supporting a positive relationship between e-tailer trust and e-loyalty, in term of increased spending [44], and intentions to purchase [45] or repurchase. E-trust also have positive and significant influence on e-commitment [46].…”
Section: Trustmentioning
confidence: 90%
“…While there has been little research expressly on contractors and clients, insight into these relations may be borrowed from studies of business-to-business (e.g., suppliers and customers) relations and research seeking to identify antecedents of dual organization and union commitment. Gournaris (2005), for example, found that mutual trust and commitment are the core elements in forging favorable relations between service providers and clients.…”
Section: Client Organization-based Antecedents Of Client Commitmentmentioning
confidence: 99%
“…Indeed, service encounter quality in a business-to-business context tends to be both overlooked at the managerial level (Bitran & Lojo 1993) and under-researched academically (Brown et al 1994;Chumpitaz & Paparoidamis 2004;Durvasula et al 1999;Gounaris 2005;Hartline & Jones 1996). This is surprising given the importance of contact personnel and the social/interpersonal aspects of the encounter in businessto-business services (Paulin et al 2000).…”
Section: Introductionmentioning
confidence: 99%